1997
DOI: 10.1046/j.1469-8137.1997.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ambient ozone on injury and yield of Phaseolus vulgaris at four rural sites in the Netherlands as assessed by using ethylenediurea (EDU)

Abstract: SUMMARYTo assess adverse effects of" ambient ozone on injury and yield, IiDU (ethylenediuvea) iind non-EDU-treated plants of bean (Phaseolus vulgaris L. cv. Lit) were exposed to ambient air at four rural sites in the Netherlands in 1994. After 6 wk of exposure, the proportion of leaves injured in non-EDU-treated plants was higher than that in plants treated with the antioxidant. A maximal degree of 3.S"r) injury was observed. Tbe highest ozone levels accumulated at eacli site for three consecutive days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Thus, our experiment demonstrated that biomass accumulation/allocation pattern is not strongly correlated with yield in B. campestris, and that there are different structure-related strategies among the cultivars to compensate for ozone-induced losses, as reviewed in Black et al (2000). Foliar application of EDU is well known to enhance plant performance and crop yield in several crops, such as potato (Eckardt and Pell, 1996), snap bean (Lee et al, 1997) and bush bean (Tonneijck and Van Dijk, 1997). Yield parameters were significantly increased with EDU treatment, indicating that ozone concentrations were sufficiently high to cause a negative effect on both cultivars.…”
Section: Differences Among the Cultivars In Growth And Edu Responsementioning
confidence: 96%
See 1 more Smart Citation
“…Thus, our experiment demonstrated that biomass accumulation/allocation pattern is not strongly correlated with yield in B. campestris, and that there are different structure-related strategies among the cultivars to compensate for ozone-induced losses, as reviewed in Black et al (2000). Foliar application of EDU is well known to enhance plant performance and crop yield in several crops, such as potato (Eckardt and Pell, 1996), snap bean (Lee et al, 1997) and bush bean (Tonneijck and Van Dijk, 1997). Yield parameters were significantly increased with EDU treatment, indicating that ozone concentrations were sufficiently high to cause a negative effect on both cultivars.…”
Section: Differences Among the Cultivars In Growth And Edu Responsementioning
confidence: 96%
“…EDU has a senescencedelaying capacity (Tonneijck and Van Dijk, 1997). Lee and Chen (1982) reported that EDU can act like the plant hormone cytokinin, with the ability to retard chlorophyll degradation, sustain protein synthesis and stimulate cell growth, but the effect is a fraction of that of a synthetic cytokinin.…”
Section: Differences Among the Cultivars In Growth And Edu Responsementioning
confidence: 99%
“…Ozone (O 3 ) is the most common phytotoxic pollutant in the USA, Europe and other industrialised areas of the world, causing adverse effects on physiology, growth and yield of agricultural crops (Tonneijack & Van Dijk, 1997; Hassan et al 1999; Madkour & Laurence, 2002; El‐Khatib, 2003; Hassan, 2004; Carrasco‐Rodriguez et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…EDU has been widely used in many parts of the world for this purpose. Some examples of plants where EDU was used include: bean (Kostka-Rick and Brunschon-Harti et al, 1995;Tonneijck and Vandijk, 1997;Elagoz and Manning, 2005), clover (Astorino et al, 1995;Tonneijck and Van Dijk, 2002), loblolly pine (Kuehler and Flagler, 1999;Manning et al, 2003), mung bean , potato (Clarke et al, 1990;Eckardt and Pell, 1996), radish Hassan et al, 1995), tobacco (Manes et al, 1990), tomato (Varshney and Rout, 1998), and turnip (Hassan et al, 1995). EDU has also been used successfully to determine ambient ozone effects on two wheat cultivars in India (Tiwari et al, 2005).…”
Section: Introductionmentioning
confidence: 99%